Global university president leadership characteristics and dynamics. Issue 10 (2nd October 2020) - Liu, Lu; Hong, Xi; Wen, Wen; Xie, Zheping; Coates, Hamish
ABSTRACT: This exploratory paper articulates the development, characteristics and nature of global university presidents and their leadership. It draws insights from a growing project which so far has involved in-depth interviews with 18 presidents of major globally focused universities. Analysing and reporting these interview results reveals the enigmatic world of presidential leadership broadens this field of research beyond the Anglosphere, helps build interpretative frameworks and perspectives, and furnished insights for guiding leadership development. The exploratory findings reinforce the particular value of studying university presidents, as these people have enormous authority, expertise and prominence.